Sputum culture and drug sensitivity testing outcome among X-pert MTB/RIF positive, rifampicin resistant sputa: a retrospective study - Kenaope, Lebogang Jacktor (My University, 2016)
Background The introduction of the X-pert MTB/Rif has shortened the time to detection of rifampicin resistant tuberculosis, which is assumed to be a surrogate for multidrug resistant tuberculosis. In practice, therefore MDR TB treatment is usually initiated soon after a rifampicin resistance result on X-pert MTB/Rif, simultaneously with a second sputum specimen, taken for confirmatory culture and further drug susceptibility testing. In this retrospective review, we report the outcome of further drug susceptibility testing performed on the second sputum specimen. Methods This study was based at the Klerksdorp Tshepong Hospital Complex. We retrospectively reviewed clinical files of patients admitted to the hospital MDR unit with rifampicin resistant TB on X-pert MTB/Rif between April 2011 and February 2014. Data from 384 patients were analysed. Only drug susceptibility testing result on the first sputum after admission was considered. Results Of 384 individual patient files with X-pert Rif resistance, MDR TB was confirmed in the subsequent culture isolates of 182(47.4%) patients (this means 176 on MTBDR plus and 6 on phenotypic DST) and on raw sputa (MTBDR plus on a sputum smear) of 5(1.3%) patients. Therefore the total number of confirmed MDR TB cases was 187(49%). Rifampicin mono-resistance, isoniazid mono-resistance and drug sensitive TB were detected in 137(36%), 12(3%) and 48(13%) patients respectively. Half [37/74(50%)] of patients with a CD4 count less than 50 cells/mm3 had rifampicin mono-resistance on culture and 4/74(5.4%) patients had isoniazid mono-resistance. Whereas patients with higher CD4 counts between 50 and 350 cells/mm3, 58/181(32%) had rifampicin mono-resistance and 4/181(2.2%) had isoniazid mono-resistance (p-0.012). Conclusion Rifampicin resistance on X-pert MTB/Rif does not always mean multidrug resistant tuberculosis will be confirmed on sputum culture. Patients with lower CD4 counts who have rifampicin resistant TB on X-pert MTB/Rif may benefit from adding INH to the standardised MDR TB regimen while awaiting confirmatory tests to confirm or rule out MDR TB.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Medicine in the branch of Internal Medicine Johannesburg, 2016
Keywords: Rifampicin Resistant Tuberculosis; X-pert MTB/Rif; Drug Sensitivity Testing; Tuberculosis